Increased cancer mortality among Japanese individuals with hyperinsulinemia - Kira, Sakurako (Metabol Open, 2020)
AIMS: To evaluate the effect of hyperinsulinemia on cancer death, we clarified the association between hyperinsulinemia and cancer mortality among Japanese individuals. METHODS: All the participants (5586 men and 6652 women) lived in Hiroshima City, underwent a 75 g oral glucose tolerance test between 1994 and 2012, and were followed for mortality until August 2013. A systematic review of death certificates was used to confirm the cause of death. RESULTS: During the follow-up period (median, 10.0 years), 587 participants died of cancer. Lung cancer was the most common cause of organ-specific death. We divided the participants into 3 groups according to the tertiles of fasting immunoreactive insulin (FIRI) levels (low, middle, and high groups). The high group had the highest mortality rate (5.5 per 1000 person-years). The hazard ratio (HR) for cancer mortality of the high group after adjustment for possible confounders, such as age, sex, body mass index, smoking status, alcohol intake, and radiation effects (model 1), was significantly higher than that of the low group (HR, 1.55; 95% confidence interval (CI), 1.23–1.95). In model 2 (model 1 plus fasting plasma glucose) and model 3 (model 1 plus HbA1c), the multivariate HRs for cancer mortality were 1.46 (95% CI, 1.15–1.85) and 1.48 (95% CI, 1.17–1.87), respectively. The HR for cancer death at high FIRI levels (per 1 μU/mL) was 1.04 (95% CI, 1.02–1.05) in all participants after adjusting for fasting plasma glucose level and other confounders. In the subgroup analysis, the HRs were 1.03 (95% CI, 0.98–1.09), 1.05 (95% CI, 1.02–1.08), and 1.04 (95% CI, 1.02–1.06) in the normal, prediabetes, and diabetes group, respectively. CONCLUSIONS: Hyperinsulinemia was associated with a high risk of cancer mortality and may be an important link between cancer mortality and diabetes or prediabetes.